Principles of anatomy and physiology - Tortora, Gerard J.; Derrickson, Bryan ;Burkett, Brendan ;Cooke, Julie ;DiPietro, Flavia;Diversi, Tara;Dye, Danielle;Engel, Alex;Green, Hayley;Macartney, Michael;McKean, Mark;Peoples, Gregory;Summers, Simon (Australia, Ltd, Milton, QLD : John Wiley & Son, Inc., 2022)
Anatomy and physiology provide us with our understandings of the body's structure and functions, and this text aims to familiarise readers with each and the ways in which they interrelate.
Chapter 1: An introduction to the human body -- 2: The chemical level of organisation -- 3: The cellular level of organisation -- 4: The tissue level of organisation -- 5: The integumentary system -- 6: The skeletal system: bone tissue -- 7: The skeletal system: the axial skeleton -- 8: The skeletal system: the appendicular skeleton -- 9: Joints -- 10: Muscular tissue -- 11: The muscular system -- 12: Nervous tissue -- 13: The spinal cord and spinal nerves -- 14: The brain and cranial nerves -- 15: The autonomic nervous system -- 16: Sensory, motor, And integrative systems -- 17: The special senses -- 18: The endocrine system -- 19: The cardiovascular system: the blood -- 20: The cardiovascular system: the heart -- 21: The cardiovascular system: blood vessels and haemodynamics -- 22: The lymphatic system and immunity -- 23: The respiratory system -- 24: The digestive system -- 25: Metabolism and nutrition -- 26: The urinary system -- 27: Fluid, electrolyte, and Acid-base homeostasis -- 28: The reproductive systems -- 29: Development and inheritance.
Includes index.
Keywords: ANATOMY